Introducing demographic changes in a model of economic growth and income distribution - Codrina Rada (The University of Utah, Department of Economics, 2009)
Unprecedented demographic changes are set to unfold in most of the industrialized world. They are relevant not only because of the diminishing pool of workers, but also because of the increasing importance of retirees as an economic class. Retirees' consumption and saving patterns can differ considerably from those of wage earners and capitalists, as retirees tend to consume more services and save less or in fact dissave. From this perspective of changing aggregate consumption and saving patterns I argue that population aging together with existing constraints to growth and the institutional framework in place leads to a reconfiguration of income distribution and therefore to possible changes in the growth rate of the economy. Understanding how future income distribution may look like and the behavior of different economic classes, helps in designing the right policies to accommodate the demographic transition.
Keywords: E12; E24; E60; 330; population aging; income distribution and growth; Keynesian macroeconomics